THE RELATIONSHIP BETWEEN NITRIC OXIDE AND GLYCEMIC CONTROL IN CONTROLLED AND UNCONTROLLED TYPE 2 DIABETES MELLITUS PATIENTS IN THE ADAM MALIK HOSPITAL MEDAN - Yessy Suziarty; Ratna Akbari Ganie; Santi Syafril (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia. Hyperglycemia and other metabolic changes can cause Nitric Oxide (NO) production disturbance. This study investigated the difference in the levels of NO and its’relationship with HbA1c in controlled and uncontrolled diabetes mellitus type 2 patients in the Adam Malik Hospital. This study was a cross-sectional study, conducted in Outpatient Clinic and Inpatient Ward of Internal Medicine Section of Endocrinology in the Adam Malik Hospital on June through October 2016, involving 70 patients type 2 Diabetes Mellitus (DM) consisting of 35 controlled type 2 diabetes patients and 35 uncontrolled type 2 diabetes patients that fulfill this study’s criteria. Nitric Oxide examination conducted by using Chemwell analyzer with the principle of double-antibody sandwich using Enzyme-Linked Immunosorbent Assay (ELISA). There was no significant relationship between HbA1c and Nitric Oxide in patients with controlled (r = 0.264) (p = 0.125) and uncontrolled (r = 0.194) (p = 0.265) type 2 diabetes mellitus. But there was a significant relationship between HbA1c and NO in patients with type 2 DM (r = 0,636) (p = 0.0001). In this study, there was no significant association between HbA1c and Nitric Oxide levels in patients with controlled and uncontrolled type 2 diabetes mellitus. There is a statistically significant relationship between HbA1C and NO in patients with type 2 diabetes.